Six Minute Walk Test: Functional Evaluation and Prognosis in Heart Failure - Mauricio de Sant Anna Jr (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
The determination of functional capacity is of fundamental importance in monitoring and defining the prognosis of patients with heart failure (HF) may be the six minute walk test (6MWT) is a possibility. The 6MWT was first described by Balke in 1963 [1], since now applied in various clinical conditions, but still without proper standardization. In 2002, the American Thoracic Society (ATS) has established a guideline for performing the 6MWT [2].  According to the ATS guidelines the 6MWT is a simple test, practical and inexpensive that aims to evaluate the functional capacity in submaximal intensity across the distance that an individual is able to go as soon as possible on a flat, hard surface in a period of six minutes. The 6MWT evaluates the overall condition and integrated responses of pulmonary, cardiovascular and neuromuscular systems and presents direct correlation with the maximal oxygen uptake (VO2max), which is described in the literature as the gold standard for determining the aerobic capacity [2].